Implementation of autonomous road navigation using camera and GPS on ATRV-mini platform - Bognot, Prado Arturo N.; Cabal, Ramlaine Jean T.; Melgarejo, Marnelli R.; Migrino, Kevin Timothy P. (2010)
Camera and GPS incorporation for a mobile robot system can provide a holistic and inexpensive approach in road navigation. This strategy has been implemented on ATRV-mini platform with the aid of an onboard computer, microcontroller, camera, GPS and sensors. The robot can be operated in two modes: autonomous and manual control. In autonomous navigation, a user assigned destination indicated by its GPS point determined the general direction of the traversal with respect to the robot's current position. The Computer Vision module produced processed camera images of the view in front of the ATRV-mini which contain directions where the platform may traverse. This data, together with the compass and Sonar output, provided the motion of the robot in its immediate vicinity. The monitoring of battery level, temperature, current GPS location, raw and processed images was displayed in a web-based user interface accessible wirelessly through the internet. Control keys are also embedded on the web interface to enable the user to manipulate the robot's movement remotely. The robot system was tested and characterized on a newly constructed road in UP Diliman Science Complex. The robot was able to successfully navigate the road and move in the direction of the indicated GPS destination coordinates. The required hardware and software components have been implemented to enable robot control and navigation in a road way. The platform and the modules mounted on it have been tested in different conditions to further characterize its functionality. A detailed discussion of the design, implementation, testing and performance of the overall system is presented in this paper. In the future, related researches may focus on the addition of features such as stereo-vision imagery, dynamic obstacle detection, car-drive platform, and pattern recognition of road symbols.
Thesis (B.S. Computer Engineering & B.S. Electronics and Communications Engineering) -- University of the Philippines, Diliman
Keywords: Autonomous robots; Mobile robots; Global positioning system; Microcontrollers; Road navigation; ATRV-mini platform